Incidence and risk factors of tuberculosis in systemic lupus erythematosus patients: a multi-center prospective cohort study - Zhang, Lifan; Zou, Xiaoqing; Jiang, Nan; Xie, Lantian; Liu, Jianghao; Yang, Zhengrong; Cao, Qifei; Li, Chunlei; Sun, Xiaochuan; Zhang, Fengchun; Zhao, Yan; Zeng, Xiaofeng; et al. (Frontiers in Immunology, 2023)
Objectives Both burdens of tuberculosis (TB) and systemic lupus erythematosus (SLE) in China are ranked as top three in the world. SLE patients are at high risk for TB, but so far, there are no guidelines for TB prevention and management targeting this population in China. This study aims to investigate the incidence of active tuberculosis (ATB) and to explore the risk factors for developing ATB in SLE patients, and to provide evidence for TB prevention and management for SLE patients in China. Methods A multi-center prospective cohort study was conducted. SLE patients were enrolled from clinics and wards of 13 tertiary hospitals in Eastern, Middle, and Western China from September 2014 to March 2016. Baseline demographic features, TB infection status, clinical information, and laboratory data were collected. ATB development was examined during follow-up visits. Kaplan-Meier method was applied to plot survival curves, and Log-rank test was used to evaluate differences. Cox proportional-hazards model was used to explore the risk factors for ATB development. Results With a median follow-up time of 58 months [interquartile range (IQR): 55-62], 16 out of 1361 SLE patients developed ATB. The 1-year incidence of ATB was 368 [95% confidence interval (CI): 46-691] per 100,000. Over a 5-year period, the cumulative incidence of ATB was 1141 [95% CI: 564-1718] per 100,000, and the incidence density was 245 per 100,000 person-years. Cox regression models were constructed with maximum daily dose of glucocorticoids (GCs) as a continuous variable and a categorical variable, respectively. In model 1, maximum daily dose of GCs (pills per day) [adjusted hazard ratio (aHR)=1.16, 95%CI: 1.04-1.30, p=0.010] and TB infection (aHR=8.52, 95%CI: 3.17-22.92, p<0.001) were independent risk factors for ATB development. In model 2, maximum daily dose of GCs≥30 mg/d (aHR =4.81, 95%CI: 1.09-22.21, P=0.038) and TB infection (aHR=8.55, 95%CI: 3.18-23.00, p<0.001] were independent risk factors for ATB development. Conclusions SLE patients had a higher incidence of ATB compared to the general population. The risk of developing ATB was even higher with increased daily dose of GCs or in a status of TB infection, in which case TB preventive treatment should be considered.